Performance assessment of the dairy co-operatives in the mainland and Saurashtra-Kutch regions of the Gujarat, India - Darshnaben P Mahida, BS Chandel, Ajmer Singh, Sendhil Ramadas, R. Malhotra, K. Ponnusamy, Kaushik Khamrui (Indian Journal of Dairy Science, 2024)
Dairy co-operatives in Gujarat (India) is a perfect case of local institution driving economic development. However, the discrepancies in its growth still exist across regions due to factors like social rigidity, bureaucratic procedures, inadequate local involvement, and management issues. The co-operative model completely failed once in the Saurashtra-Kutch region of the state and was re-established during 2007-09. Hence, the present study measures the performance of village-level dairy co-operatives societies (DCS) in the Mainland portion and Saurashtra-Kutch region of Gujarat over two periods (2011-14 & 2015-19) and proposes strategies to improve the performance. A total sample of 120 DSCs was taken from four milk unions, two from each region, and Iyengar and Sudarshan’s approach was used for calculating the composite performance index which assigns weights inversely varying with variation in the indicator. The inverse variance-based co-operative performance index analysis of 120 DCSs across two regions suggests that the Mainland region (0.269) DCSs perform better than the Saurashtra-Kutch region (0.194) and over a period, the performance has improved to 0.354 and 0.271, respectively. Further, logistic regression-based marginal effects indicated that the probability of having high financial performance is 0.278 times greater for DCS with high physical performance than the counterpart. This suggests that poor performers should diversify and intensify input and other services delivery which will raise member participation rate,